Luminescent lanthanide metal organic frameworks as chemosensing platforms towards agrochemicals and cations - Gomez, Germán Ernesto (2019)
Since the first studies of luminescent sensors based on metal organic frameworks (MOFs) about ten years ago, there has been an increased interest in the development of specific sensors towards cations, anions, explosives, small molecules, solvents, etc. However, the detection of toxic compounds related to agro-industry and nuclear activity is noticeably scarce or even non-existent. In this work, we report the synthesis and characterization of luminescent lanthanide-based MOFs (Ln-MOFs) with diverse crystalline architectures obtained by solvothermal methods. The luminescent properties of the lanthanides, and the hypersensitive transitions of Eu 3+ ( 5 D 0 → 7 F 2 ) and Tb 3+ ( 5 D 4 → 7 F 5 ) intrinsically found in the obtained MOFs in particular, were evaluated and employed as chemical sensors for agrochemical and cationic species. The limit of detection (LOD) of Tb-PSA MOFs (PSA = 2-phenylsuccinate) was 2.9 ppm for [UO 2 2+ ] and 5.6 ppm for [Cu 2+ ]. The variations of the 4f–4f spectral lines and the quenching/enhancement effects of the Ln-MOFs in the presence of the analytes were fully analyzed and discussed in terms of a combinatorial “host–guest” vibrational and “in-silico” interaction studies.